Das margens do espelho: um estudo dos reflexos da morte em primeiras estórias, de João Guimarães Rosa - Moreira, Smally Galvão (2010)
This paper is divided into three chapters, which are structured as follows: in the first chapter, we examine the figure of death and its characteristics in the context of the work of Guimarães Rosa, within a specific type, determining how this figure comes through " imposition "," no "," memory "and" ritual. " We intend to cover all the possibilities that this aspect denotes. In the second chapter, we found the incidence of the mirror as an analysis of our study, characterizing it as a stylistic condition can become a reading key, necessary for interpretation of the book "First Stories". The characterization of the mirror as an element of analysis has a theoretical foundation which stretches out along other literary works that are based on the same object. By setting the points where these works approach the theories of speculation, we want to justify their use from our perspective